2018
DOI: 10.1149/2.0371802jes
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic Analysis and Modeling of Polymer Electrolyte Fuel Cell Unsupported Catalyst Layers

Abstract: Polymer electrolyte fuel cells' (PEFCs) widespread commercialization is hindered by the devices' limited durability, in terms caused by the corrosion of the carbon support used in the Pt-based PEFC catalysts. Using unsupported electrocatalysts could mitigate such durability issues, but little is known regarding the manner in which their processing into catalyst layers (CLs) affects pore size distribution (PSD) and PEFC performance. Thus, we have used a computational model to investigate the modes of agglomerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 53 publications
(63 reference statements)
0
14
0
Order By: Relevance
“…[ 487 ] and later work by Ishikawa et al. [ 406 ] reported the use of unsupported Pt 3 Ni aerogel as a CL. The nanochain Pt 3 Ni structure adopted a tortuous gas diffusion pathway that limited performance.…”
Section: Catalyst Layer Preparation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 487 ] and later work by Ishikawa et al. [ 406 ] reported the use of unsupported Pt 3 Ni aerogel as a CL. The nanochain Pt 3 Ni structure adopted a tortuous gas diffusion pathway that limited performance.…”
Section: Catalyst Layer Preparation Methodsmentioning
confidence: 99%
“…In this case, Muzaffar et al [ 50 ] has suggested that an instructive way to categorize CLs is into two different proton transport designs: the common GDE, which requires ionomer, and flooded porous electrodes (FPEs), which do not require ionomer. [ 50,198,405 ] CL designs do not require support materials, [ 406 ] and others do not require ionomer as the thickness of the CL is small enough to utilize localized water to transfer protons without significant O 2 diffusion limitations. [ 61,197,200 ] This simplifies the CL structure, eliminating catalyst poisoning by the ionomer and the thickness of the electrode resulting in less tortuous gas transport across the CL and no O 2 diffusion resistance across the ionomer/catalyst boundary (as discussed in Section 3.4).…”
Section: Catalyst Layer Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The microstructures of the catalyst inks and CLs have been extensively studied both theoretically [ 8 , 9 ] and experimentally [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] using techniques such as conventional and cryogenic scanning and transmission electron microscopy (SEM and TEM) [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ], focused ion beam SEM (FIB-SEM) [ 17 , 18 ], atomic force microscopy [ 10 , 19 ], X-ray computed tomography [ 20 ], and X-ray [ 13 , 16 ] and neutron scattering [ 21 ]. Among the scattering techniques, anomalous small-angle X-ray scattering (ASAXS) is a powerful technique that can provide element-specific data from a multicomponent system [ 22 , 23 , 24 , 25 ] and has been used to observe the size distribution of Pt nanoparticles (NPs) in carbon-supported Pt catalysts [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the cross-section of a GDL is a three-layer structure comprising a substrate, a microporous layer (MPL), and a permeable layer in between. The substrate is a polymer supported by carbon fibers [4,5], carbon felt, carbon cloth [6] or metal foam [7,8] and filled with resins [9,10]. The MPL is usually coated with polytetrafluoroethylene (PTFE).…”
Section: Introductionmentioning
confidence: 99%